Utility of HSV Serology for Chronic Corneal Pathology. Issue 3 (May 2020) - Wang, John; Cherfan, Daniel G.; Goshe, Jeffrey M.
Abstract : Objectives: The purpose of this study is to determine the utility of obtaining herpes simplex virus (HSV) serology for patients presenting with chronic corneal pathology of unknown etiology for which HSV is a diagnostic consideration. Methods: A retrospective analysis was performed of all patients presenting to one cornea specialist (J.M.G.) between August 2011 and April 2018 with a chronic (>6 weeks) corneal condition for which HSV was suspected and serology was performed. Patient demographics, clinical presentation, treatment, final diagnosis, and follow-up duration were recorded. Results: Fifty-four patients with a median age of 52 (range: 5–85) years were included in the study. Patients were classified by presenting clinical features as corneal ulcer (46.2%), stromal keratitis (24.1%), superficial keratitis (18.5%), or keratouveitis (11.1%). The seroprevalence of HSV-1 and HSV-2 antibodies were 42.6% and 18.5%, including 5 patients (9.3%) positive for both HSV-1 and HSV-2. Serology impacted management for all patients with negative titers (48.1%), defined as discontinuing antiviral medication, electing not to start antiviral medication, or continuing antiviral medication for a non-HSV etiology (e.g., varicella zoster keratitis). No patients with HSV serology were ultimately diagnosed with HSV keratitis. Median follow-up duration was 1.5 years (range 0.8–6.6 years). Conclusion: Although only useful when negative, our study confirms that serology may be useful for excluding HSV as a diagnostic consideration for patients presenting with chronic corneal pathology. The seroprevalence of HSV antibodies for our patient cohort was comparable with previous population-based studies.